Mengoptimalkan Sumber Daya Alam untuk Kesejahteraan Masyarakat: Pendekatan Ekonomi Pancasila: Optimizing Natural Resources for Community Welfare: The Pancasila Economic Approach - Shahnas Zakiya A.; Hawa Laila Q.; Anasya Q.; Fadya Qothrun N. (Litera Academica Publishing, 2025)
Optimizing natural resources (SDA) for community welfare is the main challenge in Indonesia's economic development. The Pancasila economic approach offers a solution by prioritizing social justice and sustainability as the basis for managing natural resources. This research aims to explore the economic role of Pancasila in increasing the efficiency of natural resource utilization in order to create fair and equitable social welfare. The method used is qualitative analysis with a literature study approach, which examines the Pancasila economic theory and natural resource management practices in Indonesia. The research results show that the application of Pancasila economic principles, such as equality, shared ownership and social solidarity, can reduce economic inequality and encourage inclusive development. Management of natural resources that prioritizes community interests and environmental sustainability can create long-term prosperity. In conclusion, Pancasila economics provides a strong foundation for optimizing natural resources, focusing on fair and sustainable use, thereby supporting the achievement of social and economic prosperity for all levels of Indonesian society.